Pathophysiological roles and therapeutic potential of voltage-gated ion channels (VGICs) in pain associated with herpesvirus infection - Qiaojuan Zhang; Miguel Martin-Caraballo; Shaochung V. Hsia (Cell & Bioscience, 2020)
Abstract Herpesvirus is ranked as one of the grand old members of all pathogens. Of all the viruses in the superfamily, Herpes simplex virus type 1 (HSV-1) is considered as a model virus for a variety of reasons. In a permissive non-neuronal cell culture, HSV-1 concludes the entire life cycle in approximately 18–20 h, encoding approximately 90 unique transcriptional units. In latency, the robust viral gene expression is suppressed in neurons by a group of noncoding RNA. Historically the lesions caused by the virus can date back to centuries ago. As a neurotropic pathogen, HSV-1 is associated with painful oral lesions, severe keratitis and lethal encephalitis. Transmission of pain signals is dependent on the generation and propagation of action potential in sensory neurons. T-type Ca2+ channels serve as a preamplifier of action potential generation. Voltage-gated Na+ channels are the main components for action potential production. This review summarizes not only the voltage-gated ion channels in neuropathic disorders but also provides the new insights into HSV-1 induced pain.